THE CORRELATION BETWEEN FAMILY SUPPORT AND PREVENTION OF FAMILY NEGLECT IN FAMILY - Ezalina Ezalina; Rizanda Machmud; Nursyirwan Effendi; Yantri Maputra (Universitas Islam Negeri Alauddin Makassar, 2020)
The neglect of the elderly is a failure in providing services in terms of fulfilling their physical, psychological, and financial needs that gives negative impacts on their health. With their family support,the health of the elderly can improve so that they can enjoy life in their old age.This study aims to identify the correlation between family support and the neglect of the elderly in their family in Pekanbaru City. This studyused descriptive correlation method to 382 elderly through direct interviews. The research instrument used was a questionnaire. The data were analyzed using univariate analysis through frequency distribution and bivariate analysisusing chi square test.The results showed a high neglect of 49.74% and a low neglect of 50.26%.The type of neglect experienced by the elderly was psychological neglect namely high 59.68% and low 40.32%.The high support received by the elderly was 54,97% and the low support was 45.03%. The results of the correlation test analysis showed that there was a positive correlation between family support and neglect of the elderly with a p value of 0,000 (OR = 2.02). The results of the study conclude that the higher the support given by the family to the elderly, the lower the neglect experienced by the elderly.